2022
DOI: 10.3389/fcvm.2022.1007450
|View full text |Cite
|
Sign up to set email alerts
|

Growth stimulation expressed gene 2 (ST2): Clinical research and application in the cardiovascular related diseases

Abstract: As an interleukin (IL)-1 receptor family member, scientists found that when circulating soluble growth stimulation expressed gene 2 (sST2) is low, its ligand, IL-33, will bind to ST2L to exert protective effects on various types of cells. On the other hand, competitive binding of IL-33 occurs when sST2 concentrations are increased, followed by a reduction in the amount available for cell protection. Based on this mechanism, the usage of sST2 is to identify the population of high-risk patients with cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…IL-33 is an IL-1-like cytokine released by stromal cells in cardiac and extracardiac tissues in response to cell injury [ 130 ]. By attaching to the transmembrane receptor ST2L isoform, IL-33 produces beneficial effects such as lowering myocardial fibrosis and cardiomyocyte hypertrophy in response to angiotensin 11 or phenylephrine and apoptosis by inducing antiapoptotic factors and suppression of caspase three activities [ 131 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-33 is an IL-1-like cytokine released by stromal cells in cardiac and extracardiac tissues in response to cell injury [ 130 ]. By attaching to the transmembrane receptor ST2L isoform, IL-33 produces beneficial effects such as lowering myocardial fibrosis and cardiomyocyte hypertrophy in response to angiotensin 11 or phenylephrine and apoptosis by inducing antiapoptotic factors and suppression of caspase three activities [ 131 ].…”
Section: Reviewmentioning
confidence: 99%
“…Research has also demonstrated that as sST2 is less affected by renal function than BNP, it can be utilized in conjunction with BNP as an additional diagnostic marker for HF [ 134 ]. NTPro-BNP and sST2 both exhibited a high diagnostic accuracy for HF in a single-center study, but sST2 had an even better prediction capacity for fatal outcomes, including in-hospital and one-month mortality rates [ 130 ]. The function of sST2 in characterizing AHF in individuals presenting with acute dyspnea was examined in the PRIDE trial.…”
Section: Reviewmentioning
confidence: 99%
“…One is membrane-bound form ST2 (ST2L), which can bind to IL-33, playing a role in preventing hypertrophy and fibrosis and modulation of Th1/Th2; while the other is sST2, which acts as a decoy receptor, binding to free IL-33 and blocking ST2/IL-33 signaling (10,11). Many studies have shown that soluble ST2 is associated with the development of cardiovascular disease (CVD) such as aortic dissection, heart failure, acute coronary syndrome and atrial fibrillation (12)(13)(14)(15). The presence of inflammatory cells in coronary plaques from patients with UAP provides the basis for the atherosclerotic inflammatory hypothesis that was supported by plenty of evidence (16,17).…”
Section: Rationale and Knowledge Gapmentioning
confidence: 99%